PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus SKPD Provinsi DKI Jakarta) - Siti Chodijah; Nurul Hidayah (Universitas Mercu Buana, 2018)
ABSTRACT This study aims to determine: 1). Effect of the use of information technology on the quality of local government financial reporting, 2). The influence of the internal control system of the quality of local government financial reporting. The population in this study are part of the accounting / financial administration at SKPD in Jakarta provincial government amounting to 23 SKPD criteria Have a minimum term of one year in the period of preparation of financial statements. The data used are primary data obtained from respondents through questionnaires. Using quantitative descriptive approach. Karna, the analysis is the analysis of the data used in the form of multiple linear regression tests. The results showed that, simultaneously at variable utilization of information technology and internal control systems significant effect on the quality of local government financial reporting as evidenced from the results of simultaneous test (Test F). Partially shows the results of the use of information technology and internal control systems significant effect on the quality of local government financial reporting as evidenced from the partial test (t test). Keywords: Quality of local government financial reporting, use of information technology, internal control systems.